Virchow's Eulogies Rudolf Virchow in Tribute to his Fellow Scientists - Coghlan, Brian L. D.; Bignold, Leon P. (Birkhäuser Basel : Imprint: Birkhäuser, 2008)
Rudolph Virchow (1821-1902) was a leading figure in the medical, political and intellectual life of Germany in the second half of the nineteenth century. He became the most famous pathologist of his time, especially through his book "Cellular Pathology" - which discussed pathology in terms of the functioning of the cells in the anatomic lesions of diseases. Virchow's writings were voluminous: he wrote many books and more than 2,000 articles on medicine and anthropology alone. Despite, or perhaps because of, the volume of his writings, only a small proportion is available in English translation. Furthermore, in the translated material there has been little revealed of the man himself and his relations to others. This book is a compilation of Virchow's memorial addresses concerning other scientists of his time and related topics. To make the material easily comprehensible to the general reader, there is an introductory section to the man and his times. In addition, there are copious editors' notes to explain those events mentioned in the text which Virchow himself does not fully illuminate. This book gives a fascinating multi-dimensional view of scientists and their lives in nineteenth century Germany.